Analisis Working Capital Turnover Rasio Dan Sales Growth Rasio Terhadap Net Profit Margin Pada PT. Ramayana Lestari Sentosa, Tbk - Yati Yati; Aris Munandar; Puji Muniarty (Jurnal Manajemen Informatika & Teknologi, 2025)
The phenomenon of declining net profit amid declining sales and working capital stability indicates that there are other factors that affect the company's profitability. The purpose of this study is to determine the effect of Working Capital Turnover and Sales Growth on Net Profit Margin at PT. Ramayana Lestari Sentosa, Tbk The type of research in this study is an associative approach using qualitative methods. This study uses a list of tables that have been calculated using each variable indicator using Microsoft Excel. The data used is secondary data in the form of the company's financial statements The population used in this study is all the balance sheet and profit and loss financial statements at PT. Ramayana Lestari Sentosa, Tbk since it was listed on the IDX From 1996 to 2023 or for 27 years. The research sample from 2014 to 2023 is 10 years with the sampling technique used, namely Purposive Sampling. Data collection was carried out with documentation and literature studies then analyzed using the classical assumption test, multiple linear regression, correlation coefficient, determination test, t test and f test. The results of the study show that Working Capital Turnover and Sales Growth do not affect Net Profit Margin at PT. Ramayana Lestari Sentosa, Tbk.